1984
DOI: 10.1083/jcb.99.5.1569
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal stimulation in the exocrine pancreas results in coordinate and anticoordinate regulation of protein synthesis.

Abstract: 24-h intravenous caerulein infusion studies in the rat were combined with in vitro amino acid incorporation studies followed by high- resolution separation of proteins by two-dimensional isoelectric focusing and SDS gel electrophoresis to study the extent to which persistent changes in the biosynthesis of exocrine pancreatic proteins are regulated by cholecystokinin-like peptides. Beginning in the third hour of optimal hormone infusion at 0.25 microgram kg-1 h-1, changes were observed in the synthetic rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…It thus emerges that the relative levels of individual translation products corresponding to the above-mentioned four groups of proteins (and hence those of the mRNAs) were not correlated with the relative amounts of enzymes biosynthesized in vivo. It should be emphasized here that under the same experimental conditions, Schick et al [14] observed a 2.7-fold decrease and a 1.3-fold increase in the rate of amylase and serine protease synthesis, respectively, when caerulein was continuously infused for 6 h. These results therefore point to the existence of a translational control exerted by caerulein on pancreatic cnzyme biosynthesis during the first 6 h of enzyme stimulation.…”
Section: Qualitative Und Quuntitative Anulysis Of In Vitro Translatiomentioning
confidence: 50%
See 3 more Smart Citations
“…It thus emerges that the relative levels of individual translation products corresponding to the above-mentioned four groups of proteins (and hence those of the mRNAs) were not correlated with the relative amounts of enzymes biosynthesized in vivo. It should be emphasized here that under the same experimental conditions, Schick et al [14] observed a 2.7-fold decrease and a 1.3-fold increase in the rate of amylase and serine protease synthesis, respectively, when caerulein was continuously infused for 6 h. These results therefore point to the existence of a translational control exerted by caerulein on pancreatic cnzyme biosynthesis during the first 6 h of enzyme stimulation.…”
Section: Qualitative Und Quuntitative Anulysis Of In Vitro Translatiomentioning
confidence: 50%
“…Although infusion of caerulein has been found to induce the synthesis of a new protein, namely protein P-23 [14] (which appeared on a twodimensional gel as a discrete spot between trypsinogens I + 2 and trypsinogen 3 of molecular mass 23 kDa and isoelectric point 6), no translational product corresponding to the mRNA of protein P-23 could be detected on our autoradiography, even after 24 h of caerulein infusion. This observation is also in favour of a translational effect of the hormone on protein P-23 biosynthesis.…”
Section: Continuous Horinone Infusion For 12 and 24 Hmentioning
confidence: 75%
See 2 more Smart Citations
“…In the rat pancreas, twenty-one individual exocrine proteins have been identified by twodimensional electrophoresis : four forms of procarboxypeptidase, three forms of trypsinogen, two or three forms of amylase, two forms each of chymotrypsinogen and proelastase, one form each of lipase and RNAse (EC 3.1 .27.5), and four unidentified glycoproteins (Poort & Poort, 1981;Schick et al 1984~). In the rat, it has been demonstrated that, following treatment (5 d-3 weeks) with diets containing normal (220 g/kg)-high (820 g/kg) protein levels at the expense of carbohydrate, amylase and the majority of proteases are synthesized in direct proportion to amounts of their corresponding nutritional substrates in the diet.…”
Section: Dietary Changes and Molecular Adaptationmentioning
confidence: 99%